Banking efficiency in emerging market economies - Kent Matthews (Cardiff University, Cardiff Business School, 2010)
This paper reviews the different ways to measure bank efficiency and highlight the results of research on bank efficiency in Asian emerging economies. In particular it will outline the extent of research thus far conducted on the efficiency of banks in Pakistan and comment on how to build and improve upon them.
Keywords: 330